Group-common and individual-specific effects of structure–function coupling in human brain networks with graph neural networks - Chen, Peiyu; Yang, Hang; Zheng, Xin; Jia, Hai; Hao, Jiachang; Xu, Xiaoyu; Li, Chao; He, Xiaosong; Chen, Runsen; Okubo, Tatsuo S.; Cui, Zaixu (Imaging neuroscience (Cambridge, Mass.), 2024)
The human cerebral cortex is organized into functionally segregated but synchronized regions bridged by the structural connectivity of white matter pathways. While structure–function coupling has been implicated in cognitive development and neuropsychiatric disorders, it remains unclear to what extent the structure–function coupling reflects a group-common characteristic or varies across individuals, at both the global and regional brain levels. By leveraging two independent, high-quality datasets, we found that the graph neural network accurately predicted unseen individuals’ functional connectivity from structural connectivity, reflecting a strong structure–function coupling. This coupling was primarily driven by network topology and was substantially stronger than that of the correlation approaches. Moreover, we observed that structure–function coupling was dominated by group-common effects, with subtle yet significant individual-specific effects. The regional group and individual effects of coupling were hierarchically organized across the cortex along a sensorimotor-association axis, with lower group and higher individual effects in association cortices. These findings emphasize the importance of considering both group and individual effects in understanding cortical structure–function coupling, suggesting insights into interpreting individual differences of the coupling and informing connectivity-guided therapeutics.